Effect of Er2O3 and ErF3 on the optical properties of sodium oxyfluoroborate glasses - Hager , Ibrahim Z.; Saleh , Ibrahim A. (Scientific Journal of University of Benghazi, 2022)
Glasses based on B2O3–Na2O–NaF doped with Er2O3 and ErF3 were prepared by the melt quench technique. Density was measured and molar volume was calculated. The density and molar volume increased with the increase of Er2O3 and ErF3 content. Optical absorption spectra were measured to study the optical properties and their dependence on the Er2O3 and ErF3. The refractive index is estimated and correlated with the wavelength, Er2O3, ErF3, density, and O/F ratio. Nonlinear refractive index, optical and magnetic susceptibilities, Abbe number, molar refractivity, electronic polarizability, and energy gap were also calculated and correlated with Er2O3 and ErF3 contents.